2017
DOI: 10.1108/aeat-05-2015-0139
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance improvement of WIG aircraft

Abstract: Purpose This paper aims to investigate the aerodynamic characteristics as well as static stability of wing-in-ground effect aircraft. The effect of geometrical characteristics, namely, twist angle, dihedral angle, sweep angle and taper ratio are examined. Design/methodology/approach A three-dimensional computational fluid dynamic code is developed to investigate the aerodynamic characteristics of the effect. The turbulent model is utilized for characterization of flow over wing surface. Findings The numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…According to the numerical studies by Tahani et al (2017a), k-v SST produces the lowest error rate of lift and drag compared with measurements for flow over an airfoil in ground effect. In another work, Tahani et al (2017b) assessed different turbulence models including k-v SST, SAS and DDES over a pitching NACA-0012 airfoil in a transonic regime to investigate the accuracy of these models to predict shock-buffet and separation of boundary layer and concluded that DDES can produce better results than the other models in such flows compared with experiment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the numerical studies by Tahani et al (2017a), k-v SST produces the lowest error rate of lift and drag compared with measurements for flow over an airfoil in ground effect. In another work, Tahani et al (2017b) assessed different turbulence models including k-v SST, SAS and DDES over a pitching NACA-0012 airfoil in a transonic regime to investigate the accuracy of these models to predict shock-buffet and separation of boundary layer and concluded that DDES can produce better results than the other models in such flows compared with experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the Mach number of 0.75, computation predicts the shock location and strength. All the simulation results simulate the pressure distribution on the lower surface perfectly well (Tahani et al , 2017a, 2017b, 2017c). The results from all number of meshes predict the shock locations quite well, with a little difference in the shock strength.…”
Section: Methodsmentioning
confidence: 72%
“…Owing to the Mach number of 0.75, computation predicts the shock location and strength. All the simulation results simulate the pressure distribution on the lower surface perfectly well (Tahani et al, 2017a(Tahani et al, , 2017b, The numerical dataset for validation of this study is based on a series of articles (Brodersen et al, 2002;Laflin et al, 2005;Vassberg et al, 2007), experimental findings of ONERA wind tunnel lab (Rossow et al, 1994) (Figure 6) and a recent article on configuration of DLRF6 in ground effect (Deng et al, 2017).…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations